Konsep Keadilan dalam Teologi Islam - Zulkarnain Zulkarnain (UIN Sumatera Utara, 2021)
Abstract. This article wants to explore justice as conceptualized by Islamic theology in various disciplines. In the discussion of Islamic theology, in addition to the existence of obligations, there is also what is called rights. Related to these rights, of course it cannot be separated from what is called justice or a sense of justice. The justice contained in Islamic teachings is put forward to be indoctrinated by various scientific aspects, both philosophy, morals, theology and law. This study specifically discusses the relationship between rights and justice which are conceptualized and taught in Islamic Theology. The result is that in Islamic theology, the provision and provision of the rights of a person or group cannot be separated from the existence of an important principle, namely justice.Keywords: Justice, Theology, Islam